2019
DOI: 10.5935/0004-2749.20190002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toxic retinopathy caused by antimalarial medications with spectral domain optical coherence tomography

Abstract: | Purpose: To investigate the frequency of toxic retinopathy in patients with lupus erythematosus and rheumatoid arthritis with long-term use of chloroquine diphosphate or hydroxychloroquine through spectral domain optical coherence tomography and the outcomes of ophthalmological exams (visual acuity -Snellen's table, color vision test -Ishihara's table, fundoscopy, and retinography -red-free). Methods: A cross-sectional study was carried out involving the ophthalmologic evaluation of patients using regular ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…In the current study, the frequency of confirmed hydroxychloroquine retinopathy by using 10–12 Humphury visual field and FAF was 6.3%. This was higher than Tangtavorn et al [ 29 ] and Cabral et al [ 3 ] who found the prevalence of toxic retinopathy caused by antimalarial drugs were 3.2% and 4.15%, respectively. However, it is less than Palma Sanchez et al [ 25 ] who demonstrated in a retrospective study an overall rate of retinal toxicity (13.5%) .…”
Section: Discussioncontrasting
confidence: 55%
“…In the current study, the frequency of confirmed hydroxychloroquine retinopathy by using 10–12 Humphury visual field and FAF was 6.3%. This was higher than Tangtavorn et al [ 29 ] and Cabral et al [ 3 ] who found the prevalence of toxic retinopathy caused by antimalarial drugs were 3.2% and 4.15%, respectively. However, it is less than Palma Sanchez et al [ 25 ] who demonstrated in a retrospective study an overall rate of retinal toxicity (13.5%) .…”
Section: Discussioncontrasting
confidence: 55%
“…Among the drugs currently tested in vitro and in vivo, remdesivir, ribavirin, chloroquine (CQ) and hydroxychloroquine (HCQ) have shown promising clinical results in inhibiting the viral replication of SARS-CoV-2 (Zhang et al 2020). However, while the molecular mechanisms underlying therapeutic actions and clinical benefits remain to still be explored, the search for information regarding CQ and HCQ toxicity is a priority, since it can directly contribute to the design of randomized clinical trials (Cabral et al 2019;Jorge et al 2018;Liu et al 2020;Stokkermans and Trichonas 2019;Yam and Kwok 2006;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Side effects. Chloroquine is used as a chemoprophylactic and therapeutic agent for malaria and amebiasis 81 , while HCQ is a less toxic metabolite of chloroquine used to treat SLE, RA, etc. 82 .…”
Section: Duration Of Hospital Stay Of Hcq ± Azm Versus Standard Carementioning
confidence: 99%